2020
DOI: 10.21203/rs.3.rs-42880/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFI27 May Predict and Evaluate the Severity of Respiratory Syncytial Virus Infection in Preterm Infants

Abstract: Background: Preterm infants are a special population that vulnerable to respiratory syncytial virus (RSV) infection and the lower respiratory tract infection (LRTIs) caused by RSV could be severe and even life-threating. The purpose of the present study was to identify candidate genes of preterm infants who are susceptible to RSV infection and provide a new insight into the pathogenesis of RSV infection. Methods: Three datasets (GSE77087, GSE69606 and GSE41374) containing 183 blood samples of RSV infected pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…As a component of the anti-viral interferon response, it is not surprising that elevated IFI27 expression was observed in the blood of patients infected with a broad range of different respiratory viruses but not in the blood of patients with a bacterial respiratory infection. These data, combined with previous suggestions that IFI27 expression is associated with the severity of RSV [6, 7], suggest that IFI27 may represent a pan-viral prognostic biomarker. Interestingly, when we investigated this further in the context of influenza virus, we found that expression of IFI27L1 in the blood, rather than IFI27 itself, was associated with disease severity.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As a component of the anti-viral interferon response, it is not surprising that elevated IFI27 expression was observed in the blood of patients infected with a broad range of different respiratory viruses but not in the blood of patients with a bacterial respiratory infection. These data, combined with previous suggestions that IFI27 expression is associated with the severity of RSV [6, 7], suggest that IFI27 may represent a pan-viral prognostic biomarker. Interestingly, when we investigated this further in the context of influenza virus, we found that expression of IFI27L1 in the blood, rather than IFI27 itself, was associated with disease severity.…”
Section: Discussionsupporting
confidence: 74%
“…IFI27 (also known as ISG12 or p27) is an interferon alpha (and to a lesser extent interferon gamma) inducible gene of unknown function, with the gene product residing in the nuclear membrane of the cell [5]. IFI27 expression is associated with the severity of several different viral illnesses including respiratory syncytial virus (RSV) infection and Enterovirus 71 (EV71) hand foot and mouth disease [6,7]. Preliminary evidence suggests that IFI27 expression may be a useful biomarker for COVID-19 diagnosis and severity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptative immune responses may influence the risk of viral infections in newborns as their CD4 + T cells have delayed synthesis of IFNγ and IL-2 in presence of viral infections 40,43 . Genetic studies can be very helpful in the determination of risk factors, such as mannose-binding lectin (MBL) mutations causing MBL deficiency, which are associated with higher risk of sepsis in preterm neonates 44 , or increased IFI27 expression, associated with higher RSV infection severity 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings were significant as they were, on one hand, validated by multiple approaches (RNA-seq, qRT-PCR and GENT2 microarray database); on the other hand, they were also confirmed by multiple datasets and diverse cohorts (LCE meta-analysis database). This gene signature group contains a modulator of innate immune responses (IFN-I signal-induced gene IFI27) [34, 35], a hematopoietic transcription regulator (GATA2) [36], a metabolism mediator (ANKRD22) [37, 38], and a transcription factor involved in differentiation control (LHX4) [39], which is consistent with the following findings that immunological and metabolism mechanisms are enriched in post-treatment and responder patients ( Figure 6 A & 6B ). Moreover, several of them were proven to regulate the oncogenesis of lung cancer or respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%